The Influence of Education, Training and Work Motivation on Teacher Performance at SMP Babussalam Pekanbaru - Fitri, Riski; Gimin, Gimin; Mahdum, Mahdum (Journal Corner of Education, Linguistics, and Literature, 2024)
Teacher performance is the result of work completed by a teacher in carrying out their duties in accord with the responsibilities assigned. This research aims to determine the effect of education, training and work motivation on teacher performance of Babussalam junior high school Pekanbaru. The population in this study were 32 junior high school teachers in Babussalam which were taken by using total sampling technique. The instrument was used a questionnaire distributed. The data analysis technique used by path analysis. The results showed that the variable of teacher performance is excellent category with a score of 97%, the variable of education is doubt category with a score of 53%, the variable of training is excellent category with a score of 53%, the variable of work motivation is excellent with a score of 100%. While based on the results of the path analysis there was a significance between education on the work motivation that was 0.515, and education on the teacher performance that was 0.90, training on the work motivation that was 0.050, and training was a significance on the teacher performance that was 0.496, and then work motivation was significant on the teacher performance that was 0.478, and education was significant on the teacher performance by work motivation that was 0.255, and then training was significant on the teacher performance by work motivation that is 0.478. The suggestions are that every teacher must be able to follow the good education and apply it according to the learning of education that they have taken. And to the principal be more expected for all members of the school high motivation, attention for education and training that supports teacher performance. Thus, with better education and training followed by teachers and stronger work motivation, the higher performance will increase and the learning goals can be achieved optimally.